The Implications of the Global Financial Crisis for Low-Income Countries-An Update. (Policy Papers; Policy Paper ;, 2009)
Low-income countries are being hit hard by the global financial crisis. They are facing a sharp contraction in export growth, FDI inflows, and remittances, and lower-than-committed aid. But a marked recovery is in prospect for 2010 helped by rising world demand and supported by short-term domestic policies. Countries are using fiscal and other policies to respond to the crisis and should continue to do so, where appropriate, until the economic recovery is clearly underway. However, the risks to debt sustainability are rising and countries should begin preparing to realign policies toward medium-term sustainability once the recovery is clearly on the move. Additional highly concessional donor support is needed to ensure that countries are not forced to make these adjustments prematurely, and to facilitate a smooth return to a sustainable debt path, with strong growth, over the medium term.